2008
DOI: 10.1016/j.pain.2008.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of low back pain hospitalization – A prospective follow-up of 57,408 adolescents

Abstract: Low back pain (LBP) is common among adolescents and it has been estimated that one-fifth of adolescents suffer from recurrent severe LBP. However, longitudinal studies describing the risk factors of LBP are scarce. The purpose of this study was to investigate whether health, physical activity and other health behaviors, socio-demographic background and school success predict LBP hospitalization until early middle age. A cohort of 72,378 adolescents (57,408 respondents, response rate 79%) aged 14-18 years parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 33 publications
4
41
1
1
Order By: Relevance
“…18 The prevalence of LBP in the adolescents in our study is within the reported range in recent epidemiological studies that disclosed a lifetime prevalence ranging from 4.7% to 74.4%, 4,7,32-35 that is increasing steadily with age, approximating adult levels by around the age of 18 years and leading to hospitalization after the age of 19 years. 35 The latter seems to be evidence that LBP in adolescents is a risk factor for continuing symptoms in adulthood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…18 The prevalence of LBP in the adolescents in our study is within the reported range in recent epidemiological studies that disclosed a lifetime prevalence ranging from 4.7% to 74.4%, 4,7,32-35 that is increasing steadily with age, approximating adult levels by around the age of 18 years and leading to hospitalization after the age of 19 years. 35 The latter seems to be evidence that LBP in adolescents is a risk factor for continuing symptoms in adulthood.…”
Section: Discussionsupporting
confidence: 87%
“…60 There is a controversy regarding LBP and regular smoking. 18,61 Smoking was not shown to be a risk factor for LBP for 8% of our adolescent smokers who smoked more than 5 cigarettes daily.…”
Section: Discussionmentioning
confidence: 65%
“…Nie któ re ba da nia su ge ru ją, że brak aktyw no ści fi zycz nej jest czyn ni kiem pre dys po nu ją cym do po wsta nia bó lu krę go słu pa [22,24,27,28]. Z drugiej jed nak stro ny, in ne ba da nia wy ka za ły zwięk szone ry zy ko bó lu krę go słu pa lę dźwio we go u osób aktyw nych fi zycz nie [25,29]. Po nad to stwier dzo no wręcz szko dli wy wpływ wy so kie go po zio mu ak tywno ści fi zycz nej [30].…”
Section: Discussionunclassified
“…Certain studies have sug gested that lack of physical activity is a factor pre disposing for back pain [22,24,27,28]. However, other studies have found an increased risk of low back pain in physically active individuals [25,29]. Moreover, a harmful effect of a high level of physical activity was actually noted [30].…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain (LBP) is a common clinical entity among adolescents and adults [5,6,9,10]. The prevalence of LBP is highest in middle age, but high occurrence figures of LBP have also been reported among adolescents and young adult populations [1,2,4,14,15].…”
Section: Introductionmentioning
confidence: 99%